2022
DOI: 10.1108/apjba-08-2021-0421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perceived environmental knowledge and environmental concern on customers' green hotel visit intention: mediating role of green trust

Abstract: PurposeThe purpose of this study is twofold. First, it aims to examine the influence of customers' green considerations in the form of perceived green knowledge and environmental concern on their intention to stay at green hotels; and secondly, to explain the mediating role of green trust among the considered variables.Design/methodology/approachThe study investigates green hotel visit perceptions of 213 customers of hotel industry of Dhaka, Bangladesh using Partial Least Square method. Data was collected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 104 publications
3
27
0
1
Order By: Relevance
“…This finding supports Lam et al [ 71 ] who concluded that GT has a positive and significant impact on customer repurchase intention of green products ( β = 0.37, t = 6.60, p < 0.001). Further, this finding agreed with the finding of Sultana et al’s study [ 91 ] which demonstrated that GT has a significant positive effect on customers’ intention to stay at green hotels in Bangladesh. Another study conducted by Guerreiro and Pacheco [ 74 ] concluded that GT is significantly correlated with GWoM and GPI.…”
Section: Discussionsupporting
confidence: 92%
“…This finding supports Lam et al [ 71 ] who concluded that GT has a positive and significant impact on customer repurchase intention of green products ( β = 0.37, t = 6.60, p < 0.001). Further, this finding agreed with the finding of Sultana et al’s study [ 91 ] which demonstrated that GT has a significant positive effect on customers’ intention to stay at green hotels in Bangladesh. Another study conducted by Guerreiro and Pacheco [ 74 ] concluded that GT is significantly correlated with GWoM and GPI.…”
Section: Discussionsupporting
confidence: 92%
“…In the same vein, green purchase intention is an individual's commitment to the possibility and willingness of participating in pro-environmental behavior, e.g., visit green hotels (Eid et al, 2021) and intention is considered the best predictor of behavior (Saleem, 2021). Besides being a predictor of pro-environmental behavior, green purchase intention is also found to mediate the relationship between behavior and attitude, social norm, perceived behavioral control, and other antecedent variables (Sultana et al, 2022;Wibowo et al, 2022).…”
Section: Consumers' Green Purchase Intention To Visit Green Hotelsmentioning
confidence: 99%
“…Results also showed that the positive association between perceived environmental knowledge and green purchase intention that was shown to be valid for green hotel visits [ 51 ] was confirmed for green food too. Thus, the more people know about environmental issues, their causes, and possible solutions, the more they will be willing to buy green food.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that more knowledge about environmental issues may promote positive attitudes toward the topic [ 44 , 46 , 47 ] and consequently green consumption intention and behavior [ 48 , 49 , 50 ]. A recent study [ 51 ] reported a significant positive relationship between both perceived green knowledge and green trust and customers’ intention to visit green hotels. Furthermore, green trust mediated the relationship of customers’ green knowledge with green visit intentions.…”
Section: Introductionmentioning
confidence: 99%